Solar drying of uruguayan red gum - Ono, Andrés; Venturino, Alejandro (INNOTEC, 2011)
he use of solar energy as an alternative to non-renewable energy sources has been widely researched in the last decades. Compared to air drying, solar drying kilns can better control the drying process, resulting in a higher quality of the dry wood and lower final wood moisture content values. Investment and running costs for a solar drying kiln are lower than those of a conventional kiln. Moreover, the solar drying process can be advantageous for drying hardwoods which are traditionally considered difficult to dry such as eucalyptus wood of medium and high density (Red gums, known in Spanish as “Eucaliptos colorados”). The solar drying kiln naturally incorporates a daily high relative humidity period that can be similar to a conditioning or steaming step, although at a lower temperature. This results in fewer defects due to the drying process. A pilot scale 2.5 m3 semi-greenhouse type solar wood drying kiln was constructed at LATU (Uruguay Technological Laboratory) in Montevideo, Uruguay. The operating conditions and the results from two drying runs are presented. Two species of red gum (Eucalyptus tereticornis Sm., ADD 870 kg/m3, and Eucalyptus camaldulensis Dehnh., ADD 800 kg/m3) were dried from initial average moisture contents (WMC) of around 60% down to 10.0% and 12.7% in 108 days and 76 days, respectively. Boards were provided by the Grupo Forestal San Gregorio from trees harvested at Tacuarembo and Paysandu Departments from cattle shelter forests 60 and 70 years old. Mean volume shrinkage was 18% for E. tereticornis, and 16% for E. camaldulensis, and the level of defects was moderate. Residual stresses and moisture content gradients were observed for both species. Final moisture content values were similar compared to those obtained in conventional drying kilns but with longer drying periods and lower operating costs. This would make the solar drying process attractive to small and medium sized forest products industries in a small country like Uruguay.